Microsatellite markers in analysis of resistance to coffee leaf miner in Arabica coffee - Pereira, Gabriella Santos; Padilha, Lilian; Von Pinho, Edila Vilela Resende; Teixeira, Rita de Kássia Siqueira; de Carvalho, Carlos Henrique Siqueira; Maluf, Mirian Peres; de Carvalho, Bruna Line (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to analyze coffee (Coffea arabica) genotypes resistant to the coffee leaf miner (Leucoptera coffeella) using microsatellite markers. Sixty‑six loci were evaluated, of which 63 were obtained from the Brazilian Coffee Expressed Sequence Tag (EST) database. These loci were amplified in bulks of individuals from F5 rogenies of 'Siriema' (C. arabica x C. racemosa) resistant and susceptible to the insect, in eight samples of C. racemosa, and in a F6 population of 'Siriema' with 91 individuals segregating for resistance to the leaf miner. Polymorphisms were verified for two simple sequence repeat (SSR) loci in bulks of the susceptible progenies. The two polymorphic alleles were present in around 70% of the susceptible genotypes in F5 and in approximately 90% of the susceptible individuals in F6. However, the polymorphic EST‑SSR markers among populations contrasting for resistance to leaf miner were not correlated to the evaluated characteristics. SSR markers show inter‑ and intraspecific polymorphism in C. arabica and C. racemosa.